2018
DOI: 10.3892/etm.2018.5824
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and biochemical evaluation of the effects of quercetin on experimental sciatic nerve damage in rats

Abstract: The present study evaluated the neuroprotective and antioxidant effects of quercetin in a rat model of sciatic nerve crush injury using histopathological, morphometric and biochemical methods. A total of 48 male Sprague Dawley rats, aged 10–12 weeks old were randomly divided into eight groups, consisting of two sham groups (S-7, S-28), three quercetin-treated groups (Q-7, Q-28; 200 mg/kg/7 days), trauma (T-7, T-28; 1 min sciatic nerve crush injury) and three trauma+quercetin groups (T+Q-7, T+Q-28; trauma+querc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Morphometric analysis of the sciatic nerve sections, the myelin sheath thickness, the numbers of myelinated nerve fibers, and nerve fiber diameter was measured in five different areas from each section. All slides were photographed using a microscope (Olympus, Corporate Parkway, Center Valley, PA, USA) and photos were taken at a magnification (×10) [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Morphometric analysis of the sciatic nerve sections, the myelin sheath thickness, the numbers of myelinated nerve fibers, and nerve fiber diameter was measured in five different areas from each section. All slides were photographed using a microscope (Olympus, Corporate Parkway, Center Valley, PA, USA) and photos were taken at a magnification (×10) [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, neuroprotective and antioxidant effects of quercetin in a rat model of sciatic nerve crush injury have been explored. This work indicates the beneficial effects of quercetin in accelerating the nerve regeneration and shortening the recovery period in mild to moderate type of nerve injuries like crush injury 148.…”
Section: Phytochemicals: An Alternative Source For Available Therapeumentioning
confidence: 56%
“… 33 , 34 , 35 Attempts to enhance nerve regeneration and functional recovery with chemical compounds after SNI were also carried out in many studies. 36 , 37 In addition, studies have shown that artificial nerve conduits along with neurotrophins or stem cells can be used to regenerate peripheral nerves after injury as well. 38 , 39 , 40 , 41 On the basis of our observation of several circular RNAs differentially expressed after SNI, we hypothesized that further investigation of circular RNAs may lead to the discovery of specific functions involved in this process.…”
Section: Discussionmentioning
confidence: 99%